Factors Affecting Academic Resilience in Middle School Students: A Case Study - Rojas F., Luisa Fernanda (GIST – Education and Learning Research Journal, 2015)
This research was carried out with the purpose of identifying how and which risk and protective factors affect academic outcomes. The study explored how different family and individual environmental factors foster academic resilience. The exploratory study took place with a group of six students from a public school in Bogotá, Colombia. The school is located in a low-income and marginalized area of the city, where social problems such as poverty and violence are common. Data collection techniques included document analysis, as well as interviews with teachers and parents. The data collection was focused on identifying how academic resiliency skills can be developed in vulnerable young people. It was found that it is possible to identify and describe different protective factors from the family, such as family guidance, family support, and opportunities for meaningful family involvement that explicitly foster academic resilience in at risk-students. It was also possible to address how individual characteristics also foster positive outcomes, including optimism, perseverance, or motivation.